Work at night and breast cancer – report on evidence-based options for preventive actions - Jens Peter Bonde (Scandinavian Journal of Work, Environment & Health, 2012)

(untitled)
In 2007, the International Agency for Research on Cancer classified shift work involving circadian disruption as probably carcinogenic to humans (group 2A), primarily based on experimental and epidemiologic evidence for breast cancer. In order to examine options for evidence-based preventive actions, 16 researchers in basic, epidemiological and applied sciences convened at a workshop in Copenhagen 26–27 October 2011. This paper summarizes the evidence from epidemiological and experimental studies and presents possible recommendations for prevention of the effects of night work on breast cancer. Among those studies that quantified duration of shift work, there were statistically significant elevations in risk only after about 20 years working night shift. It is unclear from these studies whether or not there is a modest but real elevated risk for shorter durations. Hence, restriction of the total number of years working night shift could be one future preventive recommendation for shift workers. The diurnal secretion of melatonin by the pineal gland with peak in secretory activity during the night is a good biochemical marker of the circadian rhythm. Disruption of the diurnal melatonin secretion pattern can be diminished by restricting the number of consecutive night shifts. Reddish light and reduced light intensity during work at night could potentially help diminish the inhibitory activity of light with strong intensity on the melatonin secretion, but further mechanistic insight is needed before definite recommendations can be made. Earlier or more intensive mammography screening among female night shift worker is not recommended because the harm–benefit ratio in this age group may not be beneficial. Preventive effects of melatonin supplementation on breast cancer risk have not been clearly documented, but may be a promising avenue if a lack of side effects can be shown even after long-term ingestion. Women with previous or current breast cancer should be advised not to work night shifts because of strong experimental evidence demonstrating accelerated tumor growth by suppression of melatonin secretion. Work during the night is widespread worldwide. To provide additional evidence-based recommendations on prevention of diseases related to night shift work, large studies on the impact of various shift schedules and type of light on circadian rhythms need to be conducted in real work environments